Given:
![3x^2+2x=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ms3ox1is8cheffs2zf9e193ldqcqine1z7.png)
Question 2:
Let's find the values of a, b, and c.
Step 1:
Equate the equation to zero
Subtract 2 from both sides
![\begin{gathered} 3x^2+2x-2=2-2 \\ \\ 3x^2+2x-2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7z5muzmou1l2j8dfhrkchbk8znxbuh39mu.png)
To find the values of a, b, and c, apply the general quadratic formula:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
Comapre both equations:
![\begin{gathered} ax^2+bx+c=0 \\ 3x^2+2x-2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sh6yhgo7kkr7qznl2evmqn7i0l67npklml.png)
Thus, we have the following values:
a = 3
b = 2
c = -2
Question 3:
Let's solve for x
To solve for x, apply the formula:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
Substitute 3 for a, 2 for b, and -2 for c:
![\begin{gathered} x=\frac{-2\pm\sqrt[]{2^2-4(3)(-2)}}{2(3)} \\ \\ x=\frac{-2\pm\sqrt[]{4-(-24)}}{6} \\ \\ x=\frac{-2\pm\sqrt[]{4+24}}{6} \\ \\ x=\frac{-2\pm\sqrt[]{28}}{6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bshyu4u3vbzzm8zpdrtsofbztr1qisw9ay.png)
Solving further:
![\begin{gathered} x=(-2\pm5.29)/(6) \\ \\ x=(-2+5.29)/(6),\text{ }(-2-5.29)/(6) \\ \\ x=0.548,\text{ }-1.215 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/9mt8ojxwfdkfxfhp00lzlwdn4bnwsshhhy.png)
Therefore, the values of x are:
x = 0.548, -1.215
ANSWER:
2. a = 3, b = 2, c = -2
3. x = 0.548
x = -1.215